2016
DOI: 10.2340/00015555-2300
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Mammalian Target of Rapamycin Inhibitors in Vascular Anomalies: A Systematic Review

Abstract: Mammalian target of rapamycin (mTOR) inhibitors are a promising new treatment in vascular anomalies, but no published randomized controlled trials are available. The aim of this systematic review of all reported cases was to assess the efficacy and safety of mTOR inhibitors in all vascular anomalies, except cancers, in children and adults. In November 2014 MEDLINE, CENTRAL, LILACS and EMBASE were searched for studies of mTOR inhibitors in any vascular condition, except for malignant lesions, in humans. Fourtee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
4

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 102 publications
(112 citation statements)
references
References 51 publications
6
102
0
4
Order By: Relevance
“…A few recent studies have demonstrated that sirolimus had a positive effect on reducing KHE progression in patients with or without KMP . However, these findings were based on relatively small sample sizes . To confirm the effects of sirolimus in the treatment of KHE, more extensive clinical studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…A few recent studies have demonstrated that sirolimus had a positive effect on reducing KHE progression in patients with or without KMP . However, these findings were based on relatively small sample sizes . To confirm the effects of sirolimus in the treatment of KHE, more extensive clinical studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…The target concentration window of sirolimus for treatment of complicated vascular anomalies has been recently reviewed . Drug concentration targets depend on patient's clinical condition such as the type of vascular anomaly, status of disease, and patient's adverse events profile.…”
Section: Discussionmentioning
confidence: 99%
“…In the recent prospective Phase 2 study for complicated vascular anomalies, sirolimus dosed to achieve predose trough concentrations of 10–15 ng/ml was shown to be effective and safe . In other vascular anomalies treatment studies, a broader sirolimus target range of 5–15 ng/ml was reported . To accommodate both the higher and lower target concentrations, two target therapeutic windows, 10–15 and 5–10 ng/ml, were used to design the dosing regimens in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations